2014
DOI: 10.3171/2014.7.jns14283
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled dual-center trial on shunt complications in idiopathic normal-pressure hydrocephalus treated with gradually reduced or “fixed” pressure valve settings

Abstract: I dIopathIc normal pressure hydrocephalus (iNPH) is a treatable condition, first described by Hakim in 1965. 10 It is characterized clinically by gait disturbance, cognitive impairment, and urinary incontinence and radiologically by ventriculomegaly. The condition is typically diagnosed in the elderly and most often treated by insertion of a ventriculoperitoneal (VP) shunt with either a fixed or an adjustable pressure valve. Adjustable valves were designed to lower the complication rate and optimize the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 28 publications
1
37
1
1
Order By: Relevance
“…20 The reason for the apparent discrepancy between our 2 articles is that they are based on different methods. First, our current article defines the results based on a set of objective tests while the previous article was partly based on the patient's subjective descriptions of the overall effect during the followup period.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…20 The reason for the apparent discrepancy between our 2 articles is that they are based on different methods. First, our current article defines the results based on a set of objective tests while the previous article was partly based on the patient's subjective descriptions of the overall effect during the followup period.…”
Section: Discussionmentioning
confidence: 89%
“…12 The complication rate between the 2 groups (20-4 and 12) was recently published, showing no significant difference in the complication rate. 20 To our knowledge, this is the first RCT to explore the clinical effect of lowering the valve setting. Previous nonrandomized and nonblinded studies 2,4,6,27 have indicated that changing the opening pressure may have significant effects on symptoms and signs.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Such changes are not always seen in patients with leptomeningeal disease because of its acuity. 42 Nevertheless, overdrainage can occur and the neurosurgeon should be aware of such complications.…”
Section: Overdrainagementioning
confidence: 99%